2013
DOI: 10.1097/fbp.0b013e3283641ec8
|View full text |Cite
|
Sign up to set email alerts
|

Abuse liability of novel ‘legal high’ designer stimulants

Abstract: In the last few years, the variety and recreational use of 'legal high' designer stimulants has increased to unprecedented levels. Since their rapid emergence in drug markets, numerous adverse physical and psychological effects have been extensively reported. However, less is understood about the potential for compulsive use of and addiction to these drugs. Recently, a small collection of scientific studies assessing the abuse liability of these drugs has emerged. This new knowledge has been derived primarily … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 116 publications
7
17
0
Order By: Relevance
“…This escalated drug intake is a cardinal feature of the transition from drug abuse to addiction, and a sustained enhancement in drug intake produces dysregulated brain stress and executive control systems that parallel clinical observations of drug addicts [4850]. Moreover, extended access to drugs with lower abuse liability generally do not result in escalation of intake, and drug intake patterns usually remain episodic [51]. …”
Section: Laboratory Rodents Readily Self-administer Mdpv and Methylonementioning
confidence: 99%
See 3 more Smart Citations
“…This escalated drug intake is a cardinal feature of the transition from drug abuse to addiction, and a sustained enhancement in drug intake produces dysregulated brain stress and executive control systems that parallel clinical observations of drug addicts [4850]. Moreover, extended access to drugs with lower abuse liability generally do not result in escalation of intake, and drug intake patterns usually remain episodic [51]. …”
Section: Laboratory Rodents Readily Self-administer Mdpv and Methylonementioning
confidence: 99%
“…Different laboratories use a variety of stimulation parameters such as varying the intensity of the current delivered (µA), duration of pulses (msec), frequency of electrical pulse as a function of pulse / interpulse interval, and the waveform of pulses [74]. However, the two most extensively used ICSS paradigms evaluating abuse liability of psychoactive compounds are the rate-frequency curve-shift procedure [75] and the discrete-trial current threshold intensity procedure [74,76,77], the latter of which is utilized by our laboratory [46,47,51]. …”
Section: Synthetic Cathinones Increase Brain Reward Circuit Functionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of behavioral experiments suggest that synthetic cathinones and BZP could have abuse and addiction potential in humans. Thus, it was found that MDPV, mephedrone, and methylone were self-administrated in rats; the same action was exerted by BZP in rhesus monkeys (Aarde, Angrish, et al, 2013, Aarde, Huang, Creehan, Dickerson, & Taffe, 2013Fantegrossi, Winger, Woods, Woolverton, & Coop, 2005;Watterson, Watterson, & Olive, 2013). Mephedrone produced conditioned place preference in various species and lowered intracranial self-stimulation thresholds in mice (Gregg & Rawls, 2014).…”
Section: Pharmacology and Metabolismmentioning
confidence: 80%